Sub-acute pathological effects of calcium carbide as an artificial fruit ripening agent on various organs of albino mice - Ajileye, Ayodeji Blessing; Ogunbinu, Oluwapelumi Abigail; Naomi Alanza, Michael (Journal of Medical Science, 2024)
Introduction. Calcium carbide is the most commercially used artificial fruit ripener because it is inexpensive to produce though, involving the use of hazardous elements and can easily be purchased in local markets. This study aimed at investigating the architectural changes of organs extracted from albino mice fed with fruits that were ripened with calcium carbide. Material and methods. About 40 mice of both males and females, weighing between 18g-25g were randomly used for this study. They were divided into five (5) groups, made up of six mice namely Groups 1, 2, 3, 4 & 5 respectively.  A set of unripe mature pawpaw and banana were ripened with calcium carbide (CCRP & CCRB) and were fed orally to groups 3 and 5 respectively for four weeks with water. Another set of the unripe mature pawpaw and banana were ripened naturally (NRP & NRB) without subjecting them to any artificial ripening processes and were fed orally to groups 2 and 4 mice respectively for four weeks with water. Rat feed and water were also given to the control group 1.Results. Increased body weights were observed in the calcium carbide ripened banana (CCRB) treated group when compared to the other groups (control and calcium carbide ripened pawpaw). Histological sections revealed increased numbers of inflammatory cells, presence of collapsed epithelial layer, ruptured muscle, disorganized clara cells, aggregation of fibroblasts in the lungs; mild interstitial edema in the brain between the cardiocytes: mononuclear cell infiltration with cloudy swelling of the renal epithelium; dendritic cells in the brain.Discussion and conclusions. According to this study, eating fruits that are ripened with calcium carbide has adverse related health effects thus negatively altering the histological architecture of the organs such as the lungs, liver, kidney, heart as well as the brain. Fruit vendors must therefore use caution when applying calcium carbide and adhere to international regulations that strictly limit its use.